Ruminal Fistulation and Cannulation: A Necessary Procedure for the Advancement of Biotechnological Research in Ruminants - Castillo, Cristina (Animals (Basel), 2021)
SIMPLE SUMMARY: This article addresses the role of ruminal fistulation and cannulation as an essential procedure in the advancement of research related to several items: fermentation in the ruminant forestomach, effects of new food sources, rumen diseases as well as the minimization of methane emissions, implicated in the so-called greenhouse gases. The aim is also to diminish the alarmist news promoted by animalist sectors, which accuse this technique of being an act of cruelty. This paper describes the importance of this procedure as a necessary in vivo tool for biotechnological research. In addition, we highlight the necessary management measures to ensure animal welfare. This review ends with a description of current in vitro methods as an alternative to in vivo studies, assessing their applicability as a complementary tool to the knowledge of rumen dynamics. ABSTRACT: Rumen content is a complex mixture of feed, water, fermentation products, and living organisms such as bacteria, fungi, and protozoa, which vary over time and with different feeds. As it is impossible to reproduce this complex system in the laboratory, surgical fistulation and cannulation of the rumen is a powerful tool for the study (in vivo and in situ) of the physiology and biochemistry of the ruminant digestive system. Rumen fistulation in cattle, sheep, and goats has been performed extensively to advance our understanding of digestive physiology and development, nutrient degradability, and rumen microbial populations. The literature reports several fistulation and cannulation procedures in ruminants, which is not the focus of this paper. However, this method questions the ethical principles that alter the opinions of certain animal groups or those opposed to animal experimentation. In this article, we analyze the objectives of fistulation and cannulation of ruminants and the care needed to ensure that the welfare of the animal is maintained at all times. Due to the ethical issues raised by this technique, several in vitro digestion methods for simulating ruminal fermentation have been developed. The most relevant ones are described in this article. Independently of the procedure, we want to point out that research carried out with animals is obliged by legislation to follow strict ethical protocols, following the well-being and health status of the animal at all times.